Respuesta :

Answer:

3y - 6x -6xy + 9-8z

Step-by-step explanation:

here's your solution

=> -6y -14 -(-8yz) - 6x + 23 + 9y - 8z + 2zy

=> put like term together

=> -6y +9y -6x-8yz+2zy+23-14

=> 3y - 6x -6xy + 9-8z

hope it helps

hope it helps

Answer:

3y + 10yz - 6x - 8z + 9.

Step-by-step explanation:

-6y – 14 - (-8yz) - 6x + 23 +9y - 8z + 2zy

Bring like terms together:

=  9y - 6y + 2yz - (-8yz) - 6x - 14 + 23 - 8z

=  9y - 6y + 2yz  + 8yz - 6x - 14 + 23 - 8z

Now simplify:

= 3y + 10yz - 6x - 8z + 9.

ACCESS MORE